Immunohistochemical and FISH analysis of EGFR and its prognostic value in patients with oral squamous cell carcinoma. (11th September 2013) - Gröbe, Alexander; Eichhorn, Wolfgang; Fraederich, Meike; Kluwe, Lan; Vashist, Yogesh; Wikner, Johannes; Smeets, Ralf; Simon, Ronald; Sauter, Guido; Heiland, Max; Blessmann, Marco
<x xml:space="preserve">Abstract</x> Objectives To study immunohistochemical expression of the epithelial growth factor receptor (EGFR) in oral carcinomas and the head and neck region to examine possible associations with various features of the tumors and survival of the patients. Materials and methods Sections were made from two tissue arrays composed of 206 oral squamous cell carcinomas and 427 squamous cell carcinomas of the head and neck region, respectively, and examined for EGFR expression and Ki‐67 labeling index by means of immunohistochemistry, and for EGFR gene amplification by means of fluorescence in situ hybridization. Correlation between resulting parameters and with clinical features was evaluated using chi‐square test and Kaplan–Meyer analysis. Results A statistically significant association was observed for strong EGFR immunohistochemical (IHC) expression with advanced lymph node involvement (P = 0.02). EGFR immunohistochemical expression did not significantly correlate with patient disease specific (DS) or overall survival (OS). EGFR gene amplification was not correlated with any of the tumor features nor to survival of the patients (DS and OS). Discussion Epithelial growth factor receptor IHC expression and gene amplification might be suitable to predict locoregional control in oral squamous cell carcinoma patients but an inappropriate predictor for patients survival.